The entrance to the alcazar of Seville in the XIVth century: spatial and perceptive analysis through infographic reconstruction - Concepcion Rodriguez Moreno (EGA, 2014)
This text sets out to illustrate the perceptive analysis of a transformed historic-architectonic space, the new en trance to the Alcazar of Seville, built in the middle of XIVth century. We propose a way of approach to its functionality and symbolism from a fully sentient perspective, because we are convinced that it was built to promote specific emotions. Since the actual aspect of this access is far from its medieval appearance, we made the infographic reconstruction of the original space on the basis of a rigorous planimetric survey and strict archaeological, historical and aesthetic studies. Subsequently, we applied specific architectonic disciplines, methods and terminologies, and through careful observation of the virtual model, we tried to describe, as far as possible, the emotions, experiences and meanings that this architecture would arouse among its contemporary society.